All but gone - Trevannion, Matthew (Methuen modern plays., 2018)
"Owen may live in the present but his mind remains lodged firmly in the past. As he's forced into a relationship with a teenager with emotional behavioural problems he blurs aspects of his current life with the memories of what might have been and the opportunities and relationships that could have changed his world. Riddled with regret over the man he loved and the chance to flee rural Wales he's unable to detach himself from past mistakes"--Back cover